Discussing the Michal Pullmann´s book - Pauer, Jan; Pospíšil, Filip; Cajthaml, Petr; Mücke, Pavel (Dějiny – teorie – kritika, 2012)
Michal Pullmann’s book Konec experimentu. Přestavba a pád komunismu v Československu (The end of an Experiment. The Reconstruction and Fall of Communism in Czechoslovakia, Prague 2011, Scriptorium, 244p, ISBN978-80-87271-31-5), met in 2011—2012 a high level of media response especially on pages of the daily press and cultural weeklies. For this reason, the editors addressed several historians and anthropologists in an attempt to inspire a broader discussion on the history of normalisation and so-called ‘reconstruction’ of socialism in Czechoslovakia of 1970s and 1980s. This resulted in a discussion blog to which contributed Jan Pauer, Filip Pospíšil, Petr Cajthaml, and Pavel Mücke.